Оценка радиоэкологической критичности территории гидрографических районов Украины - Лев, Т.Д.; Пристер, Б.С.; Виноградская, В.Д.; Тищенко, О.Г.; Пискун, В.Н. (Геоінформатика, 2017)
С целью минимизации последствий крупных радиационных аварий в Украине и для планирования поставарийного мониторинга объектов окружающей среды разработана и реализована в виде геоинформационных процедур методология превентивной оценки степени радиоэкологической критичности территории Украины на государственном уровне. При разработке учитывались природные экологические характеристики в рамках гидрографического районирования территории Украины с выделением районов речных бассейнов и суббассейнов. Проведены геоинформационное моделирование и оценка радиоэкологической критичности одной из составляющих водосборных территорий — сельскохозяйственных земель Украины с выделением наиболее критичных зон по формированию дозы радиоактивного облучения ¹³⁷Cs на население вследствие аварийных ситуаций на атомных электростанциях. Использование методологии позволит принимать оптимальные управленческие решения о внедрении и проведении мероприятий по контролю продукции и защите населения в случае аварийных ситуаций. З метою мінімізації наслідків великих радіаційних аварій в Україні і планування поставарійного моніторингу об’єктів навколишнього середовища розроблено та реалізовано у вигляді геоінформаційних процедур методологію превентивного оцінювання ступеня радіоекологічної критичності території України на державному рівні. Методологію розроблено з урахуванням природних екологічних характеристик у межах гідрографічного районування території України з виділенням районів річкових басейнів і підбасейнів. Проведено геоінформаційне моделювання та оцінювання радіоекологічної критичності однієї зі складових водозбірних територій - сільськогосподарських земель України з виділенням найкритичніших зон з формування дози радіоактивного опромінення ¹³⁷Cs на населення внаслідок аварійних ситуацій на атомних електростанціях. Використання методології дасть змогу ухвалювати оптимальні управлінські рішення щодо впровадження та проведення заходів стосовно контролю продукції і захисту населення в разі аварійних ситуацій. Purpose. The purpose of the article is to develop a methodology of preventive assessment of potential radioecological criticality (landscape ability to intensive accumulation of radionuclides in plant products), and to apply it in hydrographic zones in Ukraine at the state level, using GIS; to minimize the consequences of a large radiation accident in Ukraine by allocating radio-ecologically dangerous areas to monitor the environment in real-time and implementing priority rehabilitation steps on agricultural land. The use of modern GIS technologies allows us to preliminary obtain a spatial presentation of the potential radiation situation formation, taking into account the influence of the territory local features on the processes of transport, deposition and migration of radionuclides by the food chain, and the formation of internal dose exposure for the population.
Design/methodology/approach. The methodology was developed based on the basin-landscape principle, taking into account the environmental and natural features of the territory. We used the results of the geo-information analysis of digital maps (relief, basin, underlying surface, land use, etc.) and environmental parameters that determine the radio-ecological characteristics of the area. Assessment of the degree of criticality zone was carried out using a complex integral index, which is calculated as the sum of weighted average radio-ecological parameters for the selected typological objects (type of soil in each basin).
Findings. We have prepared the thematic maps with the assessment of the degree of potential radio-ecological criticality of Ukraine, and the tables showing a complex index for hydrographic regions, areas of the criticality classes, and the population of these areas. The developed method allows us to analyze land use at different spatial scales with the expansion of the number of environmental parameters and spatial specification.
Practical value/implications. GIS modeling and a radio-ecological criticality assessment of the catchment areas components - agricultural land in Ukraine - permit to define the most critical areas for the formation of a radiation doseof ¹³⁷Cs for the population due to a nuclear disaster at the power plant. The obtained findings on the radio-ecologically potentially dangerous areas (the basins of the Pripyat and Desna rivers) can help to create the optimal environmental conditions for economic activities and provide safety of the native environmental objects in the regions.